Physical characteristics of drumlins, with implications for their formation, at an active drumlin field, Múlajökull, Iceland - McCracken, Reba (2015)
Despite approximately 150 years of research on drumlins, no consensus on how they form has emerged: their origin is probably the longest-standing problem in glacial geology. Solving this problem would answer important questions about the basal conditions of past and modern sediment-based ice masses and their dynamics. Although many models of drumlin formation have been proposed, in the last several decades those that involve deformation of a till bed have received the most attention. In these models subglacial growth of hills is in response either to effective stress heterogeneity in the bed or to flow instability at the ice-till interface. The forefield of Múlajökull—a warm-based, surge-type glacier in central Iceland—comprises the only known field of drumlins shaped by a modern glacier and provides an opportunity to study the stratigraphy, patterns of sediment deformation, and past effective stress distributions in and around these drumlins. Their geometric characteristics fall within ranges for Pleistocene drumlins (Johnson et al., 2010; Benediktsson et al., submitted), but glaciological conditions during drumlin formation are better known than for the Pleistocene drumlin fields that have been the focus of most previous work. This study combines field measurements, laboratory analyses of fabrics based on till anisotropy of magnetic susceptibility (AMS), consolidation testing, and analysis of aerial photos and LiDAR data from the Múlajökull forefield. Data indicate that the drumlins formed by both erosion and deposition. (1) Attitudes of basal till units that constitute drumlins and patterns of till deformation within them indicate that deposition occurred on drumlin slopes. (2) Clast and AMS fabrics in drumlins and interdrumlin areas are dominated by shear strain, with no evidence of the longitudinal compression or extension necessary if sediment flux divergence in a deforming bed caused drumlin relief. (3) The package of basal tills that dominates the stratigraphy of the drumlins thickens with proximity to ...